Congenital hepatic fibrosis (a case report) - Popovych, O. O.; Moroz, L. V.; Avdosiev, Yu. V.; Chabanov, F. A.; Voinalovych, O. O. (Zaporozhye Medical Journal, 2021)
Congenital hepatic fibrosis (CHF) is an autosomal recessive disorder of intrauterine morphogenesis of the portobiliary system, characterized by periportal fibrosis and defective remodeling of the bile ducts. The article describes the features of the clinical course, diagnosis and treatment of type I CHF in the different terms of a patient’s life: from birth to her pregnancy, during pregnancy and after childbirth. The aim of this work is to familiarize specialists with the problem of diagnosis and treatment of type I CHF in a patient with a provisional misdiagnosis of cryptogenic liver cirrhosis. Results. The features of type I CHF that determine a wider diagnostic testing in long-term unspecified liver pathology cases were identified. First-time decompensation of portal hypertension (PH) occurred at 35 weeks of gestation with the development of ascitic-edematous syndrome, hypersplenism, preeclampsia without signs of hepatic encephalopathy (HE). Cesarean section was performed at 37 weeks’ gestation and healthy baby was born. One year and 9 months after delivery, hypersplenism compensation was achieved by performing splenic artery embolization (SAE). There were no clinical manifestations of HE throughout the follow-up period. Conclusions. The diagnostic algorithm for a long-term compensated unspecified liver pathology with PH should confirm or rule out CHF. Type I CHF patients can give birth to a healthy child. SAE successfully compensates for hypersplenism and PH in type I CHF. Transient elastography is an effective method for the assessment of liver fibrosis progression in patients with type I CHF.